The Influence Of Digitalization, Welfare, And Work Environment On Employee Performance At Jember Police Resort With Job Satisfaction As An Intervening Variable - Adam Adam; Trias Setyowati; Haris Hermawan (UNIVED Press, 2026)
This study investigates the effect of digitalization, welfare, and work environment on employee performance at Jember Police Resort, with job satisfaction as a mediating variable. The research uses a quantitative survey approach with structured questionnaires distributed to employees of Jember Police Resort. Data were analyzed using Structural Equation Modeling with WarpPLS to test direct and indirect relationships among variables. The results show that digitalization, welfare, and work environment have a positive and significant effect on both job satisfaction and employee performance. Job satisfaction also has a positive and significant effect on employee performance and mediates the influence of digitalization, welfare, and work environment on performance. These findings highlight the importance of strengthening digital work systems, improving employee welfare, and creating a supportive work environment to enhance job satisfaction and performance in police organizations.